The Effect of Auricular Acupressure on Uterine Contractions, Fetal Heart Rate, and Length of Labor in the Active Phase of Primigravida - Setiawandari Setiawandari; Yuni Khoirul Waroh (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
The still high maternal mortality rate (MMR) in Indonesia, especially in East Java, is caused by indirect causes or other causes such as prolonged labor, so a method is needed to treat cases of prolonged labor such as auricular acupressure. Auricular acupressure (AKAR) is a non-pharmacological method proven effective for uterine contractions, but its side effects on the fetal heart rate (FHR) are unknown. The research aimed to analyze the AKAR method on uterine contractions, FHR, and labor duration in the first stage's active phase. This type of research is truly experimental, with a pretest-posttest control group design. The research subjects were 41 respondents, primigravida active phase first-stage mothers, selected by consecutive sampling and randomly divided into two groups, namely 21 AKAR groups and 20 deep breathing relaxation control groups. The research results of the Friedman test statistical test ρ-value equal 0.000 in the AKAR group and ρ-value equal 0.000 in the control group, meaning that AKAR influences uterine contractions. The Friedman Test findings show that AKAR does not affect FHR (ρ-value equal 0.618). The Independent Sample Test ρ-value equal 0.29 indicates no statistically significant difference between the two groups' labor lengths throughout the first stage's active phase. The AKAR group's average labor time in the first stage of the active phase was 365.40 minutes, with a minimum of 267 minutes and a high of 395 minutes. Conclusion: The auricular acupressure method affects uterine contractions but does not affect the fetal heart rate. There was no difference in the length of labor in the first active phase of labor between the auricular acupressure and deep breathing relaxation groups, so it is recommended that the auricular acupressure method can be used as an alternative complementary care to prevent prolonged labor.